2014
DOI: 10.1051/0004-6361/201423620
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances in Galactic planetary nebulae withSpitzerspectra

Abstract: We present new low-resolution (R ∼ 800) optical spectra of 22 Galactic planetary nebulae (PNe) with Spitzer spectra. These data are combined with recent optical spectroscopic data available in the literature to construct representative samples of compact (and presumably young) Galactic disc and bulge PNe with Spitzer spectra. Attending to the nature of the dust features -C-rich, O-rich, and both C-and O-rich dust features (or double chemistry) -seen in their Spitzer spectra, the Galactic disc and bulge PNe are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 69 publications
2
44
0
Order By: Relevance
“…A tight correlation is found between Ne and O abundances similar to that found in all other sample of PNe and H ii regions (Henry 1989;García-Hernández & Górny 2014;García-Rojas et al 2016). The linear fit for PNe is 12 + log(Ne/H) = (1.74 ± 0.49) × (12 + log(O/H)) − (6.60 ± 4.05), with R 2 = 0.70.…”
Section: Ne/o Abundance Ratiossupporting
confidence: 78%
“…A tight correlation is found between Ne and O abundances similar to that found in all other sample of PNe and H ii regions (Henry 1989;García-Hernández & Górny 2014;García-Rojas et al 2016). The linear fit for PNe is 12 + log(Ne/H) = (1.74 ± 0.49) × (12 + log(O/H)) − (6.60 ± 4.05), with R 2 = 0.70.…”
Section: Ne/o Abundance Ratiossupporting
confidence: 78%
“…5.4. (Henry 1989;García-Hernández & Górny 2014). This has been interpreted as Ne not being strongly altered by AGB evolution so that O and Ne grow in lock-step during the chemical evolution of galaxies.…”
Section: He N and Omentioning
confidence: 99%
“…From the analysis of a sample of Galactic disk and bulge double chemistry (DC), O-rich dust (OC), and C-rich dust (CC) PNe, García-Hernández & Górny (2014) found that the average Ne/O at Z = 0.02 for their DC and OC PNe was slightly larger than those predicted by the models by Karakas (2010) without a partial mixed zone (PMZ); therefore, they conclude that including and varying the size of a PMZ can solve the observed behaviour. However, that is exactly the opposite of what we found in our sample.…”
Section: Testing Other Stellar Evolution Modelsmentioning
confidence: 99%
“…We have compared our abundance determinations for sample A objects with the recent study made by García-Hernández & Górny (2014) for a large sample of PNe compiled from the literature. All our sample A PNe, with the exception of M 1-33 were studied by García-Hernández & Górny (2014).…”
Section: Comparison With Other Abundance Determinations In the Literamentioning
confidence: 99%
“…Low-resolution (R∼1000) optical spectroscopy of a significant portion of this sample of compact Galactic disc and bulge PNe with Spitzer spectra allowed García-Hernández & Górny (2014) to derive the nebular abundances of He, N, O, Ar, Ne, S, and Cl. Remarkably, DC PNe both with crystalline and amorphous silicate dust features (DC cr and DC am+cr ) in the bulge and disc display median He and N (and N/O) abundances higher than those observed in PNe with only O-rich or C-rich dust (see Figs.…”
Section: Introductionmentioning
confidence: 99%